Yes, I’m White, But…Now What…: Cultural Competency & Deficit Perspectives in White Preservice Undergraduate Women Teachers (International Journal of Multidisciplinary Perspectives in Higher Education, 2024)
This phenomenological qualitative study used Rowe, Bennett, and Atkinson’s (1994) White Racial Consciousness Model to conceptualize racial awareness among White undergraduate female preservice teachers. Findings indicate that White preservice recognized their White racial identity, but lacked an understanding about their positionality within systems of Whiteness. They use colorblind perspectives when discussing issues of race and racism in support of an enlightenment narrative. Participants sought diversity competencies in their student teaching experiences because they suggested their teacher preparation programs and precollege experiences limited their exposure to diverse identities and settings. They held deficit perspectives about Students of Color and struggled communicating with parents. Implications for practice are included related to improvements within teacher preparation curriculum and undergraduate student development.